Human rsources for teating HIVAIDS neds, cpacities, and gaps - Bärnighausen, Till; Humair, Salal (AIDS patient care and STDs, 2007)
Despite recent international efforts to scale-up antiretroviral treatment (ART), more than 5 million people needing ART in low- and middle-income countries (LMIC) do not receive it. Limited human resources to treat HIVAIDS (HRHA) are one of the main constraints to achieving universal ART coverage. We model the gap between needed and available HRHA to quantify the challenge of achieving and sustaining universal ART coverage by 2017. We estimate the HRHA gap in LMIC using recently published estimates of ART coverage, HIV incidence, health-worker emigration rates, mortality rates of people needing ART, and numbers of HRHA needed to treat 1000 ART patients (based on review studies, 2006). We project the HRHA gap in 10 years (2017) using a simple discrete-time model with a health worker pool replenished through education and depleted through emigrationdeath; a population needing ART replenished with a given HIV incidence rate; and higher survival rates for treated populations. We analyze the effects of varying assumptions about HRHA inflows and outflows and the evolution of the HIV pandemic in three different regional base cases (sub-Saharan Africa, non-subSaharan African LMIC, and South Africa). Current ART coverage for LMIC is around 2832 and, other things equal, will drop to 1619 by 2017 with constant current HRHA production rates. A naive model, ignoring the increased survival probability resulting from ART, suggests that approximately the current number of HRHA in ART services needs to be added every year for the next ten years to achieve universal coverage by 2017. In a model accounting for increased survival of treated patients, outcomes vary by region; sub-Saharan Africa requires two times, non-subSaharan African LMIC require 1.5 times and South Africa requires more than three times their respective current HRHA population to be added every year for the next 10 years to achieve universal coverage by 2017. Even if achieved by 2017, sustaining universal coverage requires further HRHA increases until the system reaches steady state. ART coverage is sensitive to HRHA inflow and emigration. Our model quantifies the challenge of closing the HRHA gap in LMIC. It shows that strategies to achieve universal ART coverage must account for feedback due to higher survival probabilities of people receiving ART. It suggests that universal ART coverage is unlikely to be achieved and sustained with increased HRHA inflows alone, but will require decreased HRHA outflows, substantially reduced HIV incidence, or changes in the nature or organization of care. Means to decrease HRHA emigration outflows include scholarships for healthcare education that are conditional on the recipient delivering ART in a country with high ART need for a number of years, training health workers who are not internationally mobile, or changing recruitment policies in countries receiving health workers from the developing world. Effective organizational changes include those that reduce the number of HRHA required to treat a fixed number of patients. Given the large number of health workers that even optimistic assumptions suggest will be needed in ART services in the coming decades, policymakers must ensure that the flow of workers into ART programs does not jeopardize the provision of other important health services.
Gesehen am 30.06.2017